2007
DOI: 10.1517/17460441.2.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Combing databases reveals potential antibiotic producers

Abstract: The large-scale, persistent use of antibiotics has provoked microbes to evolve mechanisms to evade them. Pharmaceutical companies have found this to be counterproductive to their business economics. To maintain company interest to invest in this sector, innovative alternatives are needed. The availability of metabolic and genomic databases has opened up an avenue for such discoveries. Using these databases, potential producers of penicillin and cephalosporin have been traced. In addition, organisms that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 51 publications
0
19
0
1
Order By: Relevance
“…The high frequency of evolution of multidrug resistant bacteria has deterred scientific community involved in developing novel antibiotics. So much so that pharmaceutical companies are hesitant to make any financial investments [157][158][159]. It's rightly said, as mentioned before that to counter environmental constraints and natural selection bacterial pathogenicity has to and will evolve over time and inhibition of QS has been gauged as the ticket out of this scramble.…”
Section: Oc8hslmentioning
confidence: 99%
“…The high frequency of evolution of multidrug resistant bacteria has deterred scientific community involved in developing novel antibiotics. So much so that pharmaceutical companies are hesitant to make any financial investments [157][158][159]. It's rightly said, as mentioned before that to counter environmental constraints and natural selection bacterial pathogenicity has to and will evolve over time and inhibition of QS has been gauged as the ticket out of this scramble.…”
Section: Oc8hslmentioning
confidence: 99%
“…It is now believed that microbes have the potential arsenal necessary to counter almost all conceivable antibiotics. So much so that pharmaceutical industry is finding it counter productive to invest in this area [1]. It has pushed researchers to the edge and forced them to have a re-look on the ways to attack microbes.…”
mentioning
confidence: 99%
“…In this post genomic era, the availability of 940 bacterial, 48 archaeal and 162 eukaryotic sequenced genomes (http://www.ncbi.nlm.nih.gov/sutils/genom_ table.cgi), has infact "fl ooded" us with a large amount of data. With the use of bioinformatics tools, it has been possible to detect novel organisms with properties such as H 2 -, PHA-, antibiotic-production [144][145][146]. These studies have also revealed those organisms, which are at present categorized as "non"-producers, because they lack a gene or two of the biosynthetic pathway.…”
Section: Exploiting Natural Hgt For Engineering Biosynthetic Pathwaysmentioning
confidence: 99%